2013
DOI: 10.1186/1824-7288-39-1
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus infection in infants and correlation with meteorological factors and air pollutants

Abstract: BackgroundRespiratory Syncytial Virus (RSV) is the most important cause of severe respiratory infections in infants with seasonal epidemics. Environmental factors (temperature, humidity, air pollution) could influence RSV epidemics through their effects on virus activity and diffusion.MethodsWe conducted a retrospective study on a paediatric population who referred to our Paediatric Emergency Unit in order to analyze the correlation between weekly incidence of RSV positive cases during winter season in Bologna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
119
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(144 citation statements)
references
References 13 publications
19
119
0
3
Order By: Relevance
“…Research into combustion-related exposure complements the strategic plan (U.S. Department of Health and Human Services 2012), which includes a global environmental health initiative and a strong focus on understanding and addressing health disparities (Figure 3). The session continued by addressing the respiratory effects of exposure to elevated levels of particulate matter, which has been associated with increased frequency and severity of lower respiratory tract infections (Vandini et al 2013). Currently there is a critical gap in scientific understanding of how such exposure causes infection of the lower respiratory tract.…”
Section: Novel Approaches For Assessing Health Effects Of Combustion mentioning
confidence: 99%
“…Research into combustion-related exposure complements the strategic plan (U.S. Department of Health and Human Services 2012), which includes a global environmental health initiative and a strong focus on understanding and addressing health disparities (Figure 3). The session continued by addressing the respiratory effects of exposure to elevated levels of particulate matter, which has been associated with increased frequency and severity of lower respiratory tract infections (Vandini et al 2013). Currently there is a critical gap in scientific understanding of how such exposure causes infection of the lower respiratory tract.…”
Section: Novel Approaches For Assessing Health Effects Of Combustion mentioning
confidence: 99%
“…It has been shown that community RSV activity, such as the weekly number of RSV hospitalizations, is significantly associated with the weekly mean and minimum temperature, water vapor pressure, relative humidity, barometric pressure [191], ultraviolet B radiance [183], and the weekly mean PM 10 concentration [193], often with a time lag. Thus, environmental factors can be used to predict community RSV activity.…”
Section: Predicting Community Rsv Activitymentioning
confidence: 99%
“…Particulate matter related to air pollution is but one example of such an agent. Previous work that studied interactions between RSV and particulate matter focused on effects on the cellular inflammatory response in vitro [76][77][78][79] and on a larger scale on defining temporal relationships between air pollution exposure and virus infections and their effects on respiratory health [80,81]. From these studies, it is apparent that air pollution should be considered as a potential confounder of the effectiveness of RSV interventions.…”
Section: Rsv and Particulate Matter: An Even Tighter Bond Than Previomentioning
confidence: 99%